2011
DOI: 10.1007/s11239-011-0552-2
|View full text |Cite
|
Sign up to set email alerts
|

Profibrinolytic effect of Enzamin, an extract of metabolic products from Bacillus subtilis AK and Lactobacillus

Abstract: Fibrinolytic system impairment contributes to the development of thrombotic disease such as cardiovascular disease and stroke. Therefore, an agent that increases fibrinolytic activity may be useful for the prevention of these diseases. In this study, to explore novel profibrinolytic agents, we examined the profibrinolytic effect of Enzamin, an extract of metabolic products from Bacillus subtilis AK and Lactobacillus in vitro and in vivo. Enzamin directly enhanced plasmin activity generated by tissue-type plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, we previously demonstrated that Enzamin treatment increased t-PA activity, but not u-PA activity, in the blood of mice. We also reported that Enzamin contains the substances that strongly bind t-PA assessed by the IAsys resonance assay ( 9 ) . Therefore, it is assumed that the pro-fibrinolytic state induced by Enzamin might be associated with the improvement of insulin resistance in obese mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we previously demonstrated that Enzamin treatment increased t-PA activity, but not u-PA activity, in the blood of mice. We also reported that Enzamin contains the substances that strongly bind t-PA assessed by the IAsys resonance assay ( 9 ) . Therefore, it is assumed that the pro-fibrinolytic state induced by Enzamin might be associated with the improvement of insulin resistance in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that Enzamin displays profibrinolytic anti-thrombotic properties both in vitro and in vivo ( 9 ) . However, the effects of Enzamin on the metabolic syndrome have not yet been elucidated.…”
mentioning
confidence: 98%
See 1 more Smart Citation